Voriconazole versus isavuconazole for invasive aspergillosis: a retrospective analysis in a medically insured U.S. population (2017–2020) - Sophea Chan; Laura Leigh Stoudenmire; Xianyan Chen; Duna Zhan; Andrés F. Henao-Martínez; Daniel B. Chastain (Therapeutic Advances in Infectious Disease)
Background: While isavuconazole (ISA) has demonstrated non-inferiority to voriconazole (VCZ) for invasive aspergillosis (IA) in clinical trials, real-world comparisons are limited. Objectives: To compare treatment completion, adverse events, hospitalizations, and healthcare costs in patients treated with VCZ versus ISA for IA. Design: Retrospective cohort study using Merative MarketScan claims data (2017–2020). Methods: Adults (⩾18 years) diagnosed with IA (International Classification of Diseases, Tenth Revision, Clinical Modification (ICD-10-CM) codes) who received VCZ or ISA monotherapy were included. Treatment completion was defined as ⩾42 days of therapy. Descriptive statistics and logistic regression were used to assess outcomes and predictors of antifungal selection, adverse events, hospitalizations, and treatment completion. Results: Among 335 patients, 84% ( n  = 282) received VCZ and 16% ( n  = 53) received ISA. Baseline characteristics were comparable, although the VCZ group had higher Medicaid enrollment, and the ISA group had more patients with malignancy. Treatment completion rates were comparable (92% each, p  = 1), as were median treatment durations (VCZ: 120 days, ISA: 112 days, p  = 0.95). Adverse event rates were not significantly different (VCZ: 49%, ISA: 60%, p  = 0.18), but CNS-related events occurred more frequently with ISA (16% vs 9%, p  = 0.32). VCZ was associated with lower outpatient pharmacy costs (median $1,596.68 vs $11,000.66, p  < 0.001) and total hospitalization costs (median $40,681.89 vs $121,545.89, p  = 0.01). Malignancy was associated with lower odds of receiving VCZ (OR 0.30, p  = 0.001), and younger age predicted higher odds of treatment incompletion (OR 0.97, p  = 0.035). Female sex was associated with increased adverse event risk. Notably, VCZ use was not associated with increased adverse events or treatment incompletion. Conclusion: VCZ was prescribed five times more frequently than ISA for IA, despite similar treatment durations and completion rates. VCZ was associated with lower costs and did not increase the risk of adverse events or treatment discontinuation. These findings suggest that VCZ remains commonly used and potentially more cost-effective treatment option for IA.